Solve for y 7y^2-2y-3=0

Math
7y2-2y-3=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=7, b=-2, and c=-3 into the quadratic formula and solve for y.
2±(-2)2-4⋅(7⋅-3)2⋅7
Simplify.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Raise -2 to the power of 2.
y=2±4-4⋅(7⋅-3)2⋅7
Multiply 7 by -3.
y=2±4-4⋅-212⋅7
Multiply -4 by -21.
y=2±4+842⋅7
Add 4 and 84.
y=2±882⋅7
Rewrite 88 as 22⋅22.
Tap for more steps…
Factor 4 out of 88.
y=2±4(22)2⋅7
Rewrite 4 as 22.
y=2±22⋅222⋅7
y=2±22⋅222⋅7
Pull terms out from under the radical.
y=2±2222⋅7
y=2±2222⋅7
Multiply 2 by 7.
y=2±22214
Simplify 2±22214.
y=1±227
y=1±227
The final answer is the combination of both solutions.
y=1+227,1-227
The result can be shown in multiple forms.
Exact Form:
y=1+227,1-227
Decimal Form:
y=0.81291653…,-0.52720225…
Solve for y 7y^2-2y-3=0

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top